A Smart Self‐Powered Rope for Water/Fire Rescue. (9th November 2022) - Li, Ming; Li, Zengqing; Ye, Xiaorui; He, Wenzhan; Qu, Lijun; Tian, Mingwei
Abstract: Rescue rope plays an indispensable role in the emergency rescue. And with the continuous development of modern society, rescue rope has been gradually developed from only with the single mechanical function to the multi‐functional rescue rope. However, the lack of smart active warning for dangers usually leads to injury or even death at complex especially some extreme environment. Herein, a smart self‐powered rope is developed by integrating fiber‐based Zn battery unit and traditional rope unit based on the mature braiding technology, which performs desirable electrochemical performance (specific capacity of 31.1 mAh cm −3 and stable cycling stability of 81.95% after 1000 cycles). Moreover, the floatable self‐powered rope and thermoduric self‐powered rope are demonstrated in extreme environment to indicate their potential application for practical water/fire rescue. Therefore, smart active response is successfully realized with the integration toward fiber‐based Zn battery and rescue rope, which largely shorten the rescue time to protect the safety and health of the human body. This study provides an effective strategy of the construction of smart rope used in emergency rescue. Abstract : The lack of rescue rope with smart active warning usually leads to injury or even death in emergency rescue. Here, a smart self‐powered rope is developed by integrating fiber‐based Zn battery and traditional rope based on the mature braiding technology, performing potential application for practical water/fire rescue. This work provides an effective strategy for the construction of smart rescue rope.